A â€œRESENDSâ€ Research-Based Teaching Material Supplement Development as a Form of Studentsâ€™ Reproductive Health Care - Sa'adah, Laila Nur; Lisdiana, Lisdiana (Journal of Biology Education, 2020)
This research was aimed to analyze the advisability and the effectiveness of â€œRESENDSâ€ research-based teaching material supplement in improving the learning outcomes and fostering the studentsâ€™ reproductive health care. This research was conducted by using research and developmental methods (R&D) which refered to the modified Sugiyono (2013) steps. The result of this research showed that the advisability of â€œRESENDSâ€ research-based teaching material material was very decent (material validity 90.65%, media validity 99.2%, studentsâ€™ reponses 89%, teacher responses 96.7%). â€œRESENDSâ€ research-based teaching material supplement was effevtive in improving the studentsâ€™ learning outcomes and their care attitudes. It was proved by the percentage of studentsâ€™ classical completeness that had achieved the KKM â‰¥ 72 was 87.9%. As many as 12% of the total students belonged to high criteria of caring attitude and 88% of the total students belonged to very high criteria. The conclusion of this research was â€œRESENDSâ€ research-based teaching material supplement was decent, valid, and effective in the biological study of reproductive system material.